DARE Train-the-Trainer Pedagogy Development Using 2-Round Delphi Methodology. (31st August 2016) - Yong, Wei Wei Dayna; Kua, Phek Hui Jade; Soon, Swee Sung; Pek, Pin Pin Maeve; Hock Ong, Marcus Eng
Abstract : The Dispatcher-Assisted first REsponder programme aims to equip the public with skills to perform hands-only cardiopulmonary resuscitation (CPR) and to use an automated external defibrillator (AED). By familiarising them with instructions given by a medical dispatcher during an out-of-hospital cardiac arrest call, they will be prepared and empowered to react in an emergency. We aim to formalise curriculum and standardise the way information is conveyed to the participants. A panel of 20 experts were chosen. Using Delphi methodology, selected issues were classified into open-ended and close-ended questions. Consensus for an item was established at a 70% agreement rate within the panel. Questions that had 60%–69% agreement were edited and sent to the panel for another round of voting. After 2 rounds of voting, 70 consensus statements were agreed upon. These covered the following: focus of CPR; qualities and qualifications of trainers; recognition of agonal breathing; head-tilt-chin lift; landmark for chest compression; performance of CPR when injuries are present; trainers' involvement in training lay people; modesty of female patients during CPR; AED usage; content of trainer's manual; addressing of questions and answers; updates-dissemination to trainers and attendance of refresher courses. Recommendations for pedagogy for trainers of dispatcher-assisted CPR programmes were developed.